Impact of Peer Review on the ESL Composing Process - Salih Ahmed, Abdel Rahman Abdalla (2003)
One of the distinctive features of the process approach to writing theory is its inclusion of various identifiable stages which composition undergoes, unlike the product approach which treats the act of writing with finality. The persistence of the composing process notion for multiple drafts in text creation has called for active involvement of learners as both reviewers and feedback providers. Despite the growing research in the area of writing processes, little is known about the effects of peer review on L2 writers' perceptions and linguistic development. The present study explores the effects of peer review activities on ESL composing process practice as perceived by the learners and the ways by which these activities affect students' linguistic development. Twenty nine undergraduate matriculation students at the IIUM majoring in English language and literature participated in the study. Sixteen of these students participated in the peer review activities, while the remaining thirteen formed the comparison group. A total of 130 essays (80 essays produced during peer review activities and 50 essays during the pre test and post test stages by both groups) were collected over a period of nine weeks. Peer reviews were conducted over five sessions, and first and revised drafts were produced on five different topics of expository writing genre. The students' first and final drafts, pre test and post test essays were collected and analyzed, and a post interview and a questionnaire survey were conducted. Non-participant observation was carried out to determine the types of negotiation and interaction that occur during peer review sessions. Further, students' errors before and after exposure to peer reviews were analyzed, identified and classified. The findings indicate that the students perceived peer review as useful and effective, and that they maintained social harmony during the process of providing and getting comments and feedback. It was also discovered that the students demonstrated selectivity in incorporating peer comments and suggestions, besides displaying fewer form and content errors after the exposure to peer reviews. Peer reviews were also found to contribute to the development of learners' social skills, awareness as learners and of linguistic as well as rhetorical knowledge The study suggests that L2 learners be given more opportunities to participate in process-based composing activities. The study also suggests that there is a need for error analysis within the context of process-oriented language learning in appreciation of learners' errors as positive learning strategies and signs of learners' current language on the target language.